The Interaction Effect between Internal Control and Self Esteem on Ethical Behavior - Christina, Veronica; Lasniroha Sarumpaet, Tety; Novatiani, Ait (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the ability of the interaction between internal control and self-esteem to explain ethical behavior. The study was conducted at SKPD in Cimahi city. The sample used in this study was 110 employees. This research is explanatory research; to see the ability to moderate self-esteem, we used moderated regression analysis with SPSS software. Likert scales are used to measure attitudes. The results showed that self-esteem was able to moderate the influence of internal controls on ethical behavior